State Defense Education Management Pada Ppkn Teachers To Prepare Middle School Students Who Spirit Of Patriotism At Smp Negeri Dki Jakarta - Pandapotan Hutajulu, Bangun; Trisnamansyah, Sutaryat; Suhendraya Muchtar, Hendi; Sulastini, Rita (CV. Inara, 2022)
The background of research on state defense education for PPKn teachers is because so far the implementation has not been optimal. The obstacle is the incompetent educational human resources so that special education is needed to defend the state. The general objective is to get an overview of the management of state defense education for Civics teachers to prepare students with patriotism at SMPN Jakarta. The specific objective is to find out the planning, organization, implementation, assessment, constraints, solutions and analyze state defense education for PPKn teachers in preparing patriotic-spirited students at SMPN Jakarta. Descriptive methods and techniques of observation, interviews, study documentation. Foundation: George R. Terry's Management Theory (2014), Baidowi's State Defense Theory (2016), and Bakry's Patriotism Theory (2010). Using a qualitative approach, philosophically, follow the philosophy of reconstruction. The research subjects consisted of principals, teachers, school committees, supervisors. The results of the study (a) Planning for state defense education for PPKn teachers at SMPN Jakarta by making a work plan to be implemented right. (b). Organizing state defense education for PPKn teachers can be done to facilitate the work of each section (c) Implementation of education state defense for PPKn teachers, through the process and learning outcomes of state defense education inside and outside schools through extracurricular activities with structured independent activities (d). Assessment of state defense education for PPKn teachers, through knowledge and fostering the attitude of students with a patriotic spirit (d). The obstacles to state defense education for PPKn teachers are human resources, state defense program managers, budget, infrastructure (e). The solution for state defense education for PPKn teachers requires the leadership of a visionary, responsible principal, so as to produce graduates who have a patriotic spirit, both in input, process, output and outcome. Conclusion; State defense education management to prepare patriotic junior high school students in DKI Jakarta Province has a positive impact on improving student behavior.